2010
DOI: 10.1016/j.childyouth.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of movement for youth within an integrated continuum of residential services

Abstract: This study examined patterns of movement for youth receiving services within a continuum of intensive and restrictive residentially-based programs. Data were collected for 701 completed episodes of care within a three-program residential continuum of care over a 5 year period, and examined time within program, movement between programs, in-program disruptive behavior, and discharge status. Results showed that most youth either remained in a stable placement in the least restrictive of the programs, or followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
(60 reference statements)
3
29
0
1
Order By: Relevance
“…A related controversy in the literature surrounds whether youth are appropriately matched to level or restrictiveness of care based on clinical need (e.g., Farmer et al, 2008; Huefner et al, 2010). Although youth in group homes have high rates of maltreatment and psychiatric disorders (Chow et al, 2012; Lee & Thompson, 2009), little is known about patterns of such characteristics, including their co-occurrence, among youth in group homes and variation across levels or restrictiveness of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related controversy in the literature surrounds whether youth are appropriately matched to level or restrictiveness of care based on clinical need (e.g., Farmer et al, 2008; Huefner et al, 2010). Although youth in group homes have high rates of maltreatment and psychiatric disorders (Chow et al, 2012; Lee & Thompson, 2009), little is known about patterns of such characteristics, including their co-occurrence, among youth in group homes and variation across levels or restrictiveness of care.…”
Section: Discussionmentioning
confidence: 99%
“…Within a continuum of services framework, it is often assumed that a youth’s emotional and behavioral needs correspond with the intensity of their treatment (Barth, 2002). Indeed, certain youth may present with greater needs that require a more restrictive placement that provides more intensive services than a lower level of care can provide (Huefner, James, Ringle, Thompson, & Daly, 2010; Lieberman, 2004). However, there are inconsistent findings on the match between youth needs and level of care.…”
Section: Match Between Clinical Needs and Level Of Carementioning
confidence: 99%
“…As such, placement assignment may not always be intentional or reflect the logic on which the continuum of services is based. Regardless of these confounding factors, behavior problems are, at least in theory, viewed as an important factor that should affect both initial placement into group care as well as eventual stepping down from group care placement to less restrictive settings (Huefner, James, Ringle, Thompson, & Daly, 2010). …”
Section: Behavior Problems and Other Predictors Of Group Carementioning
confidence: 99%
“…Some studies have indicated that movement to a more restrictive placement and an increase in the severity of behavior problems are correlated (Handwerk, Friman, Mott, & Stairs, 1998; Huefner, James, Ringle, Thompson, & Daly, 2010; Nash, Thompson, & Kim, 2006). Yet there is also countervailing evidence that a substantial number of children placed into the most restrictive settings have needs that are no more severe than those of children in lower level family-based care (Breland-Noble, Farmer, Dubs, Potter, & Burns, 2005; Farmer, Mustillo, Burns, & Holdern, 2008; James, Roesch, & Zhang, 2011; Lyons, Libman-Mintzer, Kisiel, & Shallcross, 1998).…”
Section: Introductionmentioning
confidence: 99%